Dynamics of non-structural carbohydrates in three Mediterranean woody species following long-term experimental drought - Rosas, Teresa; Galiano, Lucia Lucía; Ogaya, Roma Romà; Penuelas, Josep; Martínez-Vilalta, Jordi; Penuelas, Josep; Martínez-Vilalta, Jordi (FRONTIERS IN PLANT SCIENCE, 2013)
Stored non-structural carbohydrates (NSC) have been proposed as a key determinant of drought resistance in plants. However, the evidence for this role is controversial, as it comes mostly from observational, short-term studies. Here, we take advantage of a long-term experimental throughfall reduction to elucidate the response of NSC to increased drought 14 years after the beginning of the treatment in three Mediterranean resprouter trees (Quercus ilex L., Arbutus unedo L. and Phillyrea latifolia L.). In addition, we selected 20 Q. ilex individuals outside the experimental plots to directly assess the relationship between defoliation and NSC at the individual level. We measured the seasonal course of NSC concentrations in leaves, branches and lignotuber in late winter, late spring, summer, and autumn 2012. Total concentrations of NSC were highest in the lignotuber for all species. In the long-term drought experiment we found significant depletion in concentrations of total NSC in treatment plots only in the lignotuber of A. unedo. At the same time, A. unedo was the only species showing a significant reduction in BAI under the drought treatment during the 14 years of the experiment. By contrast, Q. ilex just reduced stem growth only during the first 4 years of treatment and P latifolia remained unaffected over the whole study period. However, we found a clear association between the concentrations of NSC and defoliation in Q. ilex individuals sampled outside the experimental plots, with lower total concentrations of NSC and lower proportion of starch in defoliated individuals. Taken together, our results suggest that stabilizing processes, probably at the stand level, may have been operating in the long-term to mitigate any impact of drought on NSC levels, and highlight the necessity to incorporate long-term experimental studies of plant responses to drought.
Keywords: crown condition; Drought; Growth; long-term; non-s; non-structural carbohydrates; starch; throughfall; Throughfall manipulation

Dynamics of non-structural carbohydrates in three Mediterranean woody species following long-term experimental drought - Rosas, Teresa; Galiano, Lucia Lucía; Ogaya, Roma Romà; Penuelas, Josep; Martínez-Vilalta, Jordi; Penuelas, Josep; Martínez-Vilalta, Jordi (FRONTIERS IN PLANT SCIENCE, 2013)
Stored non-structural carbohydrates (NSC) have been proposed as a key determinant of drought resistance in plants. However, the evidence for this role is controversial, as it comes mostly from observational, short-term studies. Here, we take advantage of a long-term experimental throughfall reduction to elucidate the response of NSC to increased drought 14 years after the beginning of the treatment in three Mediterranean resprouter trees (Quercus ilex L., Arbutus unedo L. and Phillyrea latifolia L.). In addition, we selected 20 Q. ilex individuals outside the experimental plots to directly assess the relationship between defoliation and NSC at the individual level. We measured the seasonal course of NSC concentrations in leaves, branches and lignotuber in late winter, late spring, summer, and autumn 2012. Total concentrations of NSC were highest in the lignotuber for all species. In the long-term drought experiment we found significant depletion in concentrations of total NSC in treatment plots only in the lignotuber of A. unedo. At the same time, A. unedo was the only species showing a significant reduction in BAI under the drought treatment during the 14 years of the experiment. By contrast, Q. ilex just reduced stem growth only during the first 4 years of treatment and P latifolia remained unaffected over the whole study period. However, we found a clear association between the concentrations of NSC and defoliation in Q. ilex individuals sampled outside the experimental plots, with lower total concentrations of NSC and lower proportion of starch in defoliated individuals. Taken together, our results suggest that stabilizing processes, probably at the stand level, may have been operating in the long-term to mitigate any impact of drought on NSC levels, and highlight the necessity to incorporate long-term experimental studies of plant responses to drought.
The following values have no corresponding Zotero field: pub-location: PO BOX 110, LAUSANNE, 1015, SWITZERLAND publisher: FRONTIERS RESEARCH FOUNDATION accession-num: 24130568
Keywords: crown condition; Drought; Growth; long-term; non-s; non-structural carbohydrates; starch; throughfall; Throughfall manipulation

The effect of starch isolation method on physical and functional properties of Portuguese nut starches. II. Q. rotundifolia Lam. and Q. suber Lam. acorns starches - Correia, Paula Reis; Nunes, Maria Cristiana; Beirão-da-Costa, Maria Luísa (Food Hydrocolloids, 2013)
A new starch was isolated from fruits of two acorn species, Quercus rotundifolia and Quercus suber by alkaline (A3S) and enzymatic (ENZ) methods and physical and functional properties were studied. The isolation method induced changes in most of those properties in the isolated starches, mainly in resistant starch content, syneresis, pasting, thermal and rheological properties. Isolated acorn starches presented high amylose content (53e59%) and resistant starch content (30.8e41.4%). Acorn starches showed limited and similar solubility values and swelling power values, showing a gradual increase from 60 C to 90 C. The pasting temperatures ranged from 67.5 to 72.0 C and pastes did not present breakdown, which is suggestive of a high paste stability of acorn starches during heating. At ambient temperature the turbidity and syneresis values were low, but when held at freezing temperatures the syneresis signiﬁ- cantly increased. Thermal analysis revealed that the acorn starches easily undergo transition phenomena as shown by the low To and enthalpy values (4.1e4.3 J/g), these effects were more evident in starches isolated by ENZ method. Pastes are more elastic than viscous and form strong gels after cooling. Q. suber starch was shown to be more sensitive to the effect of isolation method. Generally, starch isolated by enzymatic method presented less interesting functional properties, since this isolation procedure greater affected the raw structure of starches
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: acorns; Functional properties; isolation method; rheological properties; starch; thermal properties

Starch isolation from chestnut and acorn flours through alkaline and enzymatic methods - Correia, Paula Reis; Beirão-da-Costa, Maria Luísa (Food and Bioproducts Processing, 2012)
Two different procedures were used to isolate chestnut (Castanea sativa Mill.) and acorn (Quercus suber) starch. Starch was extracted from the ﬂour of these dried fruits by: (i) low shear at alkaline pH and successively using three sieves (A3S) at different centrifugation conditions (velocity and time) and (ii) enzymatic treatment at low shear (ENZ) at a different amount/digestion time of protease. In both cases a Central Composite Rotatable Design (CCRD) was used as an experimental design. Results were treated through the Response Surface Methodology (RSM). Based on maximum yield values and the degree of purity, the best modiﬁed conditions encountered were applied in a new trial and mass balance was established for both isolation procedures. The best centrifugation conditions encountered for the A3S isolation method were 800 × g during 15min, and for the ENZ method 900 units of protease despite the incubation time, for the same centrifugation terms. The yields reached with these experimental conditions for the A3S and ENZ methods were 83.9% and 79.9% for chestnut and 88.5% and 86.9% for acorn, respectively. Isolated starches shown to be higher in purity, presented values of 98.3% and 96.3% for chestnut and 98.1% and 97.6% for acorn, respectively for the A3S and ENZ methods
The following values have no corresponding Zotero field: publisher: Institution of Chemical Engineers
Keywords: acorn; chestnut; composition; isolation method; starch; yield

Effect of Drying Temperatures on Starch-Related Functional and Thermal Properties of Acorn Flours - Correia, P R; Beirão-da-Costa, M L (Journal of Food Science, 2011)
Abstract: The application of starchy flours from different origins in food systems depends greatly on information about the chemical and functional properties of such food materials. Acorns are important forestry resources in the central and southern regions of Portugal. To preserve these fruits and to optimize their use, techniques like drying are needed. The effects of different drying temperatures on starch-related functional properties of acorn flours obtained from dried fruits of Quercus rotundifolia (QR) and Quercus suber (QS) were evaluated. Flours were characterized for amylose and resistant starch (RS) contents, swelling ability, and gelatinization properties. Drying temperature mainly affected amylose content and viscoamylographic properties. Amylograms of flours from fruits dried at 60 °C displayed higher consistency (2102 B.U. and 1560 B.U., respectively, for QR and QS). The transition temperatures and enthalpy were less affected by drying temperature, suggesting few modifications in starch structure during drying. QR flours presented different functional properties to those obtained from QS acorn flours. The effect of drying temperatures were more evident in QR.
Keywords: acorn flours; drying; Functional properties; starch; thermal analysis

Assessing the resilience of Mediterranean holm oaks to disturbances using selective thinning - López, Bernat C; Gracia, Carlos a.; SABATE, Santiago; KEENAN, Trevor (Acta Oecologica, 2009)
Climate change will increase the frequency and the intensity of droughts in the Mediterranean region, likely reducing growth and increasing mortality of holm oaks (Quercus ilex), one of the most abundant species of Mediterranean forests. In water-limited systems such as those of the Mediterranean, carbon allocation patterns strongly favour belowground accumulation, especially in large subterranean structures called lignotubers. The resilience of these forests depends largely on the replenishment rate of these carbon reserves after disturbances. An experimental thinning, with two intensities (removal of 40% and 80% of basal area), was performed in 1992 in a holm oak forest at the Prades Experimental Complex of Catchments (NE Spain). In 2002, a second thinning was carried out in subplots within the former experimental 0.5 ha plots. Samples from the lignotubers of holm oak trees were analyzed for starch, and both mobile and immobile chemical components, in order to assess the resilience of holm oaks to repeated disturbances. Our results show that after 10 years, starch stocks in the lignotubers have only recovered to half their former values. Removing 40% of the basal area instead of 80% is suggested to be the better managing option for this kind of forests.
Keywords: mediterranean forest; NIRS; Quercus ilex; resilience; resprouting; starch; thinning

Assessing the resilience of Mediterranean holm oaks to disturbances using selective thinning - López, Bernat C.; Gracia, Carlos a; SABATE, Santiago; KEENAN, Trevor (Acta Oecologica, 2009)
Climate change will increase the frequency and the intensity of droughts in the Mediterranean region, likely reducing growth and increasing mortality of holm oaks (Quercus ilex), one of the most abundant species of Mediterranean forests. In water-limited systems such as those of the Mediterranean, carbon allocation patterns strongly favour belowground accumulation, especially in large subterranean structures called lignotubers. The resilience of these forests depends largely on the replenishment rate of these carbon reserves after disturbances. An experimental thinning, with two intensities (removal of 40% and 80% of basal area), was performed in 1992 in a holm oak forest at the Prades Experimental Complex of Catchments (NE Spain). In 2002, a second thinning was carried out in subplots within the former experimental 0.5 ha plots. Samples from the lignotubers of holm oak trees were analyzed for starch, and both mobile and immobile chemical components, in order to assess the resilience of holm oaks to repeated disturbances. Our results show that after 10 years, starch stocks in the lignotubers have only recovered to half their former values. Removing 40% of the basal area instead of 80% is suggested to be the better managing option for this kind of forests.
Keywords: mediterranean forest; NIRS; Quercus ilex; resilience; resprouting; starch; thinning

Differential and interactive effects of temperature and photoperiod on budburst and carbon reserves in two co-occurring Mediterranean oaks - Sanz-Pérez, V.; Castro-Díez, P.; Valladares, F. (Plant Biology, 2009)
Effects of temperature and photoperiod and their interactions on budburst and on the use of carbon reserves were examined in two Mediterranean oaks differing in wood anatomy and leaf habit. Seedlings of Quercus ilex subsp. ballota (evergreen and diffuse-porous wood) and Q. faginea (semi-deciduous and ring-porous wood) were grown under two temperatures (12 and 19 °C) and two photoperiods (10 and 16 h) in a factorial experiment. In the 16 h photoperiod at 19 °C, photosynthesis was suppressed in half of the seedlings by covering leaves with aluminium foil. The concentration of soluble sugars, starch and lipids in leaves, stems and roots was assessed before and after budburst. Under the 12 °C treatment (mean current temperature in early spring in the Iberian Peninsula), budburst in Q. faginea occurred earlier than in Q. ilex. Higher temperature promoted earlier budburst in both species, mostly under the 16 h photoperiod. This response was less pronounced in Q. faginea because its budburst was also controlled by photoperiod, and because this species needs to construct a new ring of xylem before budburst to supply its growth demands. Therefore, dates of budburst of the two species became closer to each other in the warmer treatment, which might alter competitive relations between the species with changing climate. While Q. ilex relied on carbon reserves for budburst, Q. faginea relied on both carbon reserves and current photoassimilates. The different responses of the two Quercus species to temperature and photoperiod related more to xylem structure than to the source of carbon used for budburst.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Global warming; Lipids; Phenology; Quercus faginea; Quercus ilex; soluble sugars; starch; wood anatomy

Differential and interactive effects of temperature and photoperiod on budburst and carbon reserves in two co-occurring Mediterranean oaks - Sanz-Pérez, V; Castro-Diez, P; Valladares, F (Plant Biology, 2009)
Effects of temperature and photoperiod and their interactions on budburst and on the use of carbon reserves were examined in two Mediterranean oaks differing in wood anatomy and leaf habit. Seedlings of Quercus ilex subsp. ballota (evergreen and diffuse-porous wood) and Q. faginea (semi-deciduous and ring-porous wood) were grown under two temperatures (12 and 19 °C) and two photoperiods (10 and 16 h) in a factorial experiment. In the 16 h photoperiod at 19 °C, photosynthesis was suppressed in half of the seedlings by covering leaves with aluminium foil. The concentration of soluble sugars, starch and lipids in leaves, stems and roots was assessed before and after budburst. Under the 12 °C treatment (mean current temperature in early spring in the Iberian Peninsula), budburst in Q. faginea occurred earlier than in Q. ilex. Higher temperature promoted earlier budburst in both species, mostly under the 16 h photoperiod. This response was less pronounced in Q. faginea because its budburst was also controlled by photoperiod, and because this species needs to construct a new ring of xylem before budburst to supply its growth demands. Therefore, dates of budburst of the two species became closer to each other in the warmer treatment, which might alter competitive relations between the species with changing climate. While Q. ilex relied on carbon reserves for budburst, Q. faginea relied on both carbon reserves and current photoassimilates. The different responses of the two Quercus species to temperature and photoperiod related more to xylem structure than to the source of carbon used for budburst.
Keywords: Global warming; Lipids; Phenology; Quercus faginea; Quercus ilex; soluble sugars; starch; wood anatomy

Effects of partial defoliation on carbon and nitrogen partitioning and photosynthetic carbon uptake by two-year-old cork oak (Quercus suber) saplings - Cerasoli, S; Scartazza, A; Brugnoli, E; Chaves, M M; Pereira, J S (Tree Physiology, 2004)
At the end of the growing season in late July, 20-month-old cork oak (Quercus suber L.) saplings were partially defoliated (63% of leaf area) to evaluate their ability to recover leaf area after defoliation. At 18 and 127 days after defoliation, changes in starch and nitrogen pools were determined in leaves and perennial organs, and variations in photosynthetic carbon uptake were investigated. To determine the role of stored nitrogen in regrowth after defoliation, plant nitrogen was labeled in the previous winter by enriching the nutrient solution with 15N. Plants recovered the lost leaf area in 127 days. Although there was remobilization of starch and nitrogen from leaves and perennial organs, the availability of resources for growth in the following spring was not decreased by defoliation. On the contrary, starch concentration in coarse roots was higher in defoliated saplings than in control saplings, presumably as a result of the higher net CO2 exchange rate in newly developed leaves compared with pre-existing leaves.
10.1093/treephys/24.1.83
Keywords: 15N labeling; defoliation; Nitrogen remobilization; starch

Effects of partial defoliation on carbon and nitrogen partitioning and photosynthetic carbon uptake by two-year-old cork oak (Quercus suber) saplings - Cerasoli, S.; Scartazza, A.; Brugnoli, E.; Chaves, M. M.; Pereira, J. S. (Tree Physiology, 2004)
At the end of the growing season in late July, 20-month-old cork oak (Quercus suber L.) saplings were partially defoliated (63% of leaf area) to evaluate their ability to recover leaf area after defoliation. At 18 and 127 days after defoliation, changes in starch and nitrogen pools were determined in leaves and perennial organs, and variations in photosynthetic carbon uptake were investigated. To determine the role of stored nitrogen in regrowth after defoliation, plant nitrogen was labeled in the previous winter by enriching the nutrient solution with 15N. Plants recovered the lost leaf area in 127 days. Although there was remobilization of starch and nitrogen from leaves and perennial organs, the availability of resources for growth in the following spring was not decreased by defoliation. On the contrary, starch concentration in coarse roots was higher in defoliated saplings than in control saplings, presumably as a result of the higher net CO2 exchange rate in newly developed leaves compared with pre-existing leaves.
10.1093/treephys/24.1.8310.1093/treephys/24.1.83
Keywords: 15N labeling; defoliation; Nitrogen remobilization; starch

Structural and functional traits of Quercus ilex in response to water availability - Bussotti, Filippo; Bettini, Davide; Grossoni, Paolo; Mansuino, Silvia; Nibbi, Renzo; Soda, Costanza; Tani, Corrado (Environmental and Experimental Botany, 2002)
Water potential and morpho-anatomical parameters were measured, during the course of 1 year, on leaves of Quercus ilex trees growing in two coastal stands in Tuscany (Central Italy) with different conditions of water availability: Colognole (CL, mesic site) and Cala Violina (CV, xeric site). Morpho-anatomical measurements included: general leaf features and sclerophylly indices (surface area, thickness, mass per area and density), leaf moisture indices (water content, relative water content, succulence) and histochemical analysis (detection and localization of cutine and tannins in the leaves and starch reserves in the twigs). During the warmest and driest period (August) pre-dawn water potential (pd ) in Holm-oak leaves reached −2.7 MPa at CV and −0.6 MPa at CL. Leaf surface was lower (−34%) and total leaf thickness (+10%), as well as spongy-palisade parenchyma ratio (+20%) were higher at CV. The sclerophylly parameters (leaf mass per area and leaf tissue density) were higher at CV than at CL (+24% leaf mass per area and +19% leaf tissue density). Among the moisture parameters, water content was higher at CL (+8%) and succulence was higher at CV (+13%). No differences in relative water content were observed between the two sites. All the parameters considered were substantially stable during the study period, with the exception of relative water content at CL, that ﬂuctuated within the year. Histochemical analysis revealed a greater thickness of the upper cuticular layer at CV, whereas there were no differences in tannin distribution and content between the two sites. Differences in starch storage were detected in branchlets: it was abundant in CV but very scarce at CL. The strategies of Quercus ilex to cope with water stress were discussed at morpho-structural level.
Keywords: leaf structure; starch; Tannins; water potential

Structural and functional traits of Quercus ilex in response to water availability - Bussotti, Filippo; Bettini, Davide; Grossoni, Paolo; Mansuino, Silvia; Nibbi, Renzo; Soda, Costanza; Tani, Corrado (Environmental and Experimental Botany, 2002)
Water potential and morpho-anatomical parameters were measured, during the course of 1 year, on leaves of Quercus ilex trees growing in two coastal stands in Tuscany (Central Italy) with different conditions of water availability: Colognole (CL, mesic site) and Cala Violina (CV, xeric site). Morpho-anatomical measurements included: general leaf features and sclerophylly indices (surface area, thickness, mass per area and density), leaf moisture indices (water content, relative water content, succulence) and histochemical analysis (detection and localization of cutine and tannins in the leaves and starch reserves in the twigs). During the warmest and driest period (August) pre-dawn water potential (pd ) in Holm-oak leaves reached −2.7 MPa at CV and −0.6 MPa at CL. Leaf surface was lower (−34%) and total leaf thickness (+10%), as well as spongy-palisade parenchyma ratio (+20%) were higher at CV. The sclerophylly parameters (leaf mass per area and leaf tissue density) were higher at CV than at CL (+24% leaf mass per area and +19% leaf tissue density). Among the moisture parameters, water content was higher at CL (+8%) and succulence was higher at CV (+13%). No differences in relative water content were observed between the two sites. All the parameters considered were substantially stable during the study period, with the exception of relative water content at CL, that ﬂuctuated within the year. Histochemical analysis revealed a greater thickness of the upper cuticular layer at CV, whereas there were no differences in tannin distribution and content between the two sites. Differences in starch storage were detected in branchlets: it was abundant in CV but very scarce at CL. The strategies of Quercus ilex to cope with water stress were discussed at morpho-structural level.
Keywords: leaf structure; starch; Tannins; water potential

Effects of long-term elevated CO2 on foliage characteristics of Quercus ilex L. and Juniperus communis L. - Verkaik, E; Bartelink, H H (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
To study the effects of long-term elevated CO2 on Quercus ilex and Juniperus communis, leaves from plants growing close to a natural CO2 spring and from plants at a control site were collected and analyzed. Starch concentrations in leaves were found to be higher for plants growing under high CO2. Nitrogen concentrations were lower, but only in Juniperus communis. No differences in stomatal densities were found. The results indicate that in a CO2 -elevated environment, growth of both species will be different: Quercus ilex will be able to take advantage of the higher CO2 levels in spring, whereas in both species limited sink availability in the middle of the growing season will result in increased starch concentrations.
Keywords: CO2-springs; nitrogen; starch; stomatal density

Histology of Callogenesis and Somatic Embryogenesis Induced in Stem Fragments of Cork Oak (Quercus suber) Cultured In Vitro - MAÂTAOUI, M E L; Espagnac, H; MICHAUX-FERRIÈRE, N (Annals of Botany, 1990)
Calluses able to produce somatic embryos were formed during in vitro culture of shoot fragments of cork oak (Quercus suber L.).Histological monitoring of these fragments during culture showed that it was the cortical parenchyma cells which underwent dedifferentiation before calluses were formed by repeated divisions. The calluses consisted of parenchyma cells surrounded by a few layers of meristematic cells. Proembryos formed in groups around the edge of some calluses. Histological examination showed that they were produced by the evolution of two different categories of cell: one category had the appearance of ‘embryogenic’ cells with very thick walls, a small vacuole rich in starch and a well-developed nucleus with a prominent nucleolus. The other cells were very bulky with large vacuoles; their morphology was similar to that of suspensor cells encountered in embryogenesis in gymnosperms. The ontogenic stages were similar to those described in zygotic embryos of the genus Quercus. Nevertheless, most of the embryonic structures deviated from normal development and at all stages produced secondary proembryos.
Keywords: callogenesis; cork-oak; embryogenic cells; histology; Quercus suber L.; secondary embryogenesis; Somatic embryogenesis; starch